A mononuclear nine-coordinated Dy(iii) complex exhibiting field-induced single-ion magnetism behaviour. Issue 22 (10th May 2022) - Hu, Biao; Xi, Jing; Cen, Peipei; Guo, Yan; Ding, Yi; Qin, Yuanyuan; Zhang, Yi-Quan; Liu, Xiangyu
Abstract : Reaction of Dy(iii ) ion with tridentate acylhydrazone ligand leads to a field-induced Dy(iii ) SIM, of which the magneto-structural correlation is elucidated by the magnetic and theoretical studies. Abstract : A new mononuclear Dy(iii ) complex, with the formula [Dy(Hcpt)3 ]·2H2 O (1 ), has been successfully prepared via self-assembly between Dy(iii ) ions and 2-cyano- N ′-(1-(pyridin-2-yl)amido)acetyl (Hcpt) ligand. X-ray diffraction study shows that the Dy(iii ) ion is nine-coordinated by three Hcpt ligands with a tridentate chelating mode, leading to an approximately monocapped square-antiprismatic ( C 4v ) geometry. Magnetic data analysis demonstrates that 1 performs field-induced slow magnetic relaxation with a relaxation barrier of 97.90 K, due to the quantum tunneling effect suppressed upon a static dc field of 2000 Oe. To deeply understand the magnetic behaviors, the relaxation mechanisms and magneto-structure relationship are rationally discussed using ab initio calculations as well.